Pengembangan Modul Pembelajaran Interaktif Fisika Terintegrasi Etnosains Peresean pada Materi Hukum Newton - Muhammad Khairul Yusni; Lalu Ahmad Didik Meiliyadi; Ilham (Alpatih Harapan Semesta, 2026)
Physics learning at the secondary school level faces challenges, particularly students’ low interest and difficulty in understanding abstract concepts. Physics is often perceived as a difficult and less engaging subject, which may contribute to low learning achievement. Therefore, innovative and contextual learning resources are needed to enhance students’ engagement and understanding. However, learning modules integrating Peresean ethnoscience into Newton's Laws learning are still limited. This study aims to develop and evaluate an interactive physics module integrated with local ethnoscience values in terms of validity, effectiveness, and practicality. The research employed the Research and Development (R&D) method using the 4D development model consisting of define, design, develop, and disseminate stages. Data were collected through expert validation sheets, student learning achievement tests, and student response questionnaires. The results showed that the developed module was categorized as valid, with validity scores of 0.873 from material experts and 0.762 from media experts. The module effectively improved students’ learning outcomes, indicated by an N-Gain score of 0.760 in the high category. Furthermore, students gave a positive response with a practicality score of 88.79%. Thus, the interactive physics module integrated with local ethnoscience is feasible for use as a learning resource at the secondary school level.